UJI EFEK ANTIPIRETIK EKSTRAK ETANOL DAUN TEMBELEKAN (LANTANA CAMARA L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Suwertayasa, I Made Putra; Bodhi, Widdhi; Edy, Hosea Jaya (PHARMACON, 2013)
ABSTRACTTembelekan leaves (Lantana camara L.) contains flavonoids that possess antipyretic activityto inhibit prostaglandin. The aim of this study was toexamine the effect of ethanolic extractfrom tembelekan leaves as antipyreticon white male rats strain Wistar induced with DPT-Hb.This study is arandomized complete experimental design. Tested animals were 15 white malewistar rats, weighing 130-180g. Test ed animals were divided into 5 groups : negative group(CMC suspension 2.5ml), positive group (paracetamol), and treatment group of tembelekanleaves extract 720mg/kgBB, 1080mg/kgBB and 1440mg/kgBB. Temperature measurementswere conducted before the rats induced with DPT-Hb, 1 hour after administered with DPTeanalyzed by ANOVA and LSD (Least significant different). The conclusion of this study isethanolic extract from Tembelekan leaves (Lantana camara L.) possess antipyretic activiryon white male rats strain Wistar.Keywords: Tembelekan Leaves, Antipyretics, DPT-HB, Rats